2020
DOI: 10.3390/biom10101356
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-1 Promotes Hepatocyte-Like Differentiation of Hepatoma Cells Targeting Ets-1 and AP-1

Abstract: Syndecan-1 is a transmembrane heparan sulfate proteoglycan which is indispensable in the structural and functional integrity of epithelia. Normal hepatocytes display strong cell surface expression of syndecan-1; however, upon malignant transformation, they may lose it from their cell surfaces. In this study, we demonstrate that re-expression of full-length or ectodomain-deleted syndecan-1 in hepatocellular carcinoma cells downregulates phosphorylation of ERK1/2 and p38, with the truncated form exerting an even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 101 publications
1
5
0
Order By: Relevance
“…Their amounts can increase or decrease, while they can also be regulated by glycosylation or sulfation [ 74 ]. Our previous results confirmed that the differentiation of hepatoma cell lines after syndecan-1 transfection acted together with the changes of an HS pattern to a more sulfated one, as indicated by HS-specific antibodies, capable of interfering with the promoter activation of AP1 and Ets1 [ 16 , 75 ]. Such complexity of regulation may account, at least in part, for their often-contradictory behavior.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Their amounts can increase or decrease, while they can also be regulated by glycosylation or sulfation [ 74 ]. Our previous results confirmed that the differentiation of hepatoma cell lines after syndecan-1 transfection acted together with the changes of an HS pattern to a more sulfated one, as indicated by HS-specific antibodies, capable of interfering with the promoter activation of AP1 and Ets1 [ 16 , 75 ]. Such complexity of regulation may account, at least in part, for their often-contradictory behavior.…”
Section: Discussionsupporting
confidence: 79%
“…Our previous experiments indicated that SDC1, the major proteoglycan of the liver, is capable of inducing hepatocyte-like differentiation of hepatoma cell lines [ 16 ], and HS chains in the healthy human liver can interfere with DNA-binding transcription factors [ 23 ]. Together, these results suggested that the regulatory functions of SDC1 in the liver may be far more extensive than previously thought.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal, non-cancerous hepatocytes are characterized by the presence of syndecan, which silences MAPK signalling (TLN1, SPTAN1). 107 To summarize, it should be stated that the nfND did not unambiguously affect the behaviour of HepG2 cells, on the one hand, its pro-tumour potential can be presumed; however, strong activation of oxidative phosphorylation and reduced migration of these cells may indicate the continuation of research with some modifications to the nfND.…”
Section: Dovepressmentioning
confidence: 91%
“…However, the exact role and diagnostic significance of SORBS1 in BRCA are not yet clear. Syndecan-1 (SDC1, also known as CD138) is a key regulator of fatty acid synthesis and catalyzes the formation of mono-unsaturated fatty acids (MUFA) from saturated fatty acids (SFA) [87][88][89][90] .SDC1 has been implicated in various cancers, including BRCA [91][92][93][94] . The inactivation of SDC1 can lead to the consumption of unsaturated fatty acids, thereby inhibiting cancer cells 90,95,96 .…”
Section: Prognostic Gene-drug Interaction Network Analysismentioning
confidence: 99%